Analisis Efektifitas Dan Kontribusi Pajak Reklame Terhadap Pendapatan Asli Daerah Kota Bandar Lampung Tahun 2020-2022 Pada Badan Pengelolaan Pajak Dan Retribusi Daerah Kota Bandar Lampung - Jordi , Roy; Novila Sari, Pipit; Silvia, Dewi (LPPM STIE KRAKATAU, 2024)
The realization of local revenue from 2020-2022 has increased and decreased. Local revenue is a source of funds obtained within its own territory consisting of local tax revenue, local levy revenue, other legitimate local revenue and revenue from returns. This research uses a type of qualitative data that is time series using secondary data. The research was conducted at the Tax And Levy Management Agency (BPPRD) Bandar Lampung City. The population of this research billboard tax realization and target report Bandar Lampung City in the year 2020-2022. The sample of this research is billboard tax realization and target report Bandar Lampung City in the year 2020-2022. Data processing includes tabulation and data processing. The results of this study are that the effectiveness of the target report of Bandar Lampung Township in the 2020 fiscal year is 82.98% quite effective, the 2021 fiscal year is 87.84% quite effective, the 2022 fiscal year is 93.19% effective, and the total effectiveness obtained by the billboard tax realization is 88.00% quite effective based on the effectiveness criteria. The contribution of Advertisiment Tax to the Original Revenue of Bandar Lampung City in the year 2020 is low, in the year 2021 it is low, and in the year 2022 it is low, and the contribution rate of 4.90% is still low under the contribution criterion